Origin of Visible Light Photocatalytic Activity of Ag3AsO4 from First-Principles Calculation - Yan Gong; Hongtao Yu; Xie Quan (International Journal of Photoenergy)
Recently a novel sliver oxide Ag3AsO4 has been found to be an excellent photocatalyst with strong oxidation capability for pollutant degradation under visible light. But the origin of its high visible light photocatalytic activity was unclear which hindered further research of Ag3AsO4. For clarifying that, the electronic structure and optical properties of Ag3AsO4 have been analyzed by the hybrid density functional method. The results reveal that the Ag3AsO4 presents a narrow band gap with strong oxidation ability of the valence bands maximum edge and the highly delocalized charge distribution of the conduction bands minimum is beneficial for the carriers transfer to surface to participate in the photocatalytic reaction. These results provide clear explanations of the excellent visible light photocatalytic performance of the Ag3AsO4 from microscopic aspect. And it is significant to design novel materials with high photocatalytic performance.